2011
DOI: 10.1590/s0102-311x2011000800005
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos psicossociais do trabalho e dor musculoesquelética em professores

Abstract: Investigou-se a associação entre aspectos psicossociais do trabalho e queixas de dor musculoesquelética (DME) em professores. Um estudo censitário de corte transversal investigou 4.496 professores da rede municipal de ensino infantil e fundamental de Salvador, Bahia, Brasil. Informações sobre queixas de dor musculoesquelética em membros superiores, membros inferiores e dorso (variáveis dependentes), categorias do Modelo Demanda-Controle (variáveis independentes) e covariáveis foram coletadas num questionário p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
25

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 29 publications
2
35
0
25
Order By: Relevance
“…Apesar do dado observado com relação ao trabalho em alta exigência, cabe mencionar que outras pesquisas evidenciaram que trabalhadores com alta exigência apresentam as reações mais adversas à saúde, produtividade e satisfa-ção 22,39,40,41 . Portanto, o achado de situação favorável à qualidade de vida em trabalho de alta exigência deve ser analisado cuidadosamente em função das características específicas do tipo de trabalho analisado.…”
Section: Discussionunclassified
“…Apesar do dado observado com relação ao trabalho em alta exigência, cabe mencionar que outras pesquisas evidenciaram que trabalhadores com alta exigência apresentam as reações mais adversas à saúde, produtividade e satisfa-ção 22,39,40,41 . Portanto, o achado de situação favorável à qualidade de vida em trabalho de alta exigência deve ser analisado cuidadosamente em função das características específicas do tipo de trabalho analisado.…”
Section: Discussionunclassified
“…Although the relationship between MSP and working conditions of teachers has not been the object of this work, other studies claim that working conditions are determinants of health impairment among teachers. The prevalence of MSP is related to variables of teaching activities, including working time, number of students per class, weekly schedule, physical exertion, heat, furniture, high demand and low decision-making capacity 4,23 . The conditions under which the work is performed by educators can be a source of personal wear with consequent impairment of perception of well-being at work [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated using Statcalc Epi Info software (version 6.04) and took into account the 55% prevalence of musculoskeletal pain 4 , and maximum error of 5% for a 95% significance level. A 10% addition in values was made to compensate for any loss or incomplete questionnaires, resulting in a minimum sample size of 356 subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, as from the1990s, there has been increase in the number of studies investigating working conditions and health of professors. Cardoso et al 15 , in a census study with 4496 professors of the city of Salvador, have identified that work overload, together with unfavorable psychosocial aspects of the working environment, may lead to the development or worsening of chronic conditions, such as pain. In this study, chronic pain was a relevant health problem among professors, being associated to impaired labor activity with decreased performance or withdrawal from work activities 15 .…”
Section: Introductionmentioning
confidence: 99%